Curcumin-polymeric nanoparticles against colon-26 tumor-bearing mice: Cytotoxicity, pharmacokinetic and anticancer efficacy studies - Chaurasia S.; Chaubey P.; Patel R.R.; Kumar N.; Mishra B. (My University, 2025)
Context: Curcumin (CUR), can inhibit proliferation and induce apoptosis of tumor cells, its extreme insolubility and limited bioavailability restricted its clinical application. Objective: An innovative polymeric nanoparticle of CUR has been developed to enhance the bioavailability and anti-cancer efficacy of CUR, in vitro and in vivo. Materials and methods: Cationic copolymer Eudragit E 100 was selected as carrier, which can enhance properties of poor bioavailable chemotherapeutic drugs (CUR). The CUR-loaded Eudragit E 100 nanoparticles (CENPs) were prepared by emulsification-diffusion-evaporation method. The in vitro cytotoxicity study of CENPs was carried out using sulphorhodamine B assay. Pharmacokinetic and anti-cancer efficacy of CENPs was investigated in Wister rats as well as colon-26 tumor-bearing mice after oral administration. Results: CENPs showed acceptable particle size and percent entrapment efficiency. In vitro cytotoxicity studies in terms of 50% cell growth inhibition values demonstrated ~19-fold reduction when treated with CENPs as compared to pure CUR. ~91-fold increase in Cmax and ~95-fold increase in AUC0–12h were observed indicating a significant enhancement in the oral bioavailability of CUR when orally administered as CENPs compared to pure CUR. The in vivo anti-cancer study performed with CENPs showed a significant increase in efficacy compared with pure CUR, as observed by tumor volume, body weight and survival rate. Conclusions: The results clearly indicate that the developed polymeric nanoparticles offer a great potential to improve bioavailability and anticancer efficacy of hydrophobic chemotherapeutic drug. © 2015 Taylor & Francis.